The Impact of Writing Intensive Professional Development on High School Teachersa Science Content Knowledge of Energy in Systems (Global Journal of Human-Social Science, 2013)
The Communication in Science Inquiry Project CISIP investigated the impact of writing intensive inquiry based professional development on high school teachers science content knowledge of Energy in Systems In particular we investigated whether different forms of assessment provided different information about the depth of teacher knowledge We developed a two-tier Energy Test linked to both national and state science standards which was administered both before and after science teacher particip-ation in 23 hours of professional development on energy in biological and societal systems Our study found that we were successful in relaying content knowledge to the teachers When we analyzed misconceptions in distracter choices and written responses on the same test however we found we were successful in some areas but not in others The application of knowledge gained about energy in systems through writing scientific explanations was the least successful of all
Keywords: earth science education; professional development; energy in systems; scientific explanations; scientific literacy